A geographic distribution database of the cassava whitefly complex (Hemiptera, Aleyrodidae) and their associated parasitoids and hyperparasitoids (Hymenoptera) - Vásquez Ordoñez, Aymer Andrés; Hazzi, Nicolas A; Escobar Prieto, David; Paz-Jojoa, Dario; Parsa, Soroush (2015)
Whiteflies (Hemiptera, Aleyrodidae) are represented by more than 1500 herbivorous species around the world. Some of them are notorious pests of cassava (Manihot esculenta), a primary food crop in the tropics. Whitefly populations are regulated mainly by Hymenopteran parasitoids. Despite their importance, neither the distribution of cassava whiteflies, nor that of their associated parasitoids, is well documented. This paper therefore reports observational and specimen-based occurrence records of cassava whiteflies and their associated parasitoids and hyperparasitoids. The dataset consists of 1,311 distribution records documented by the International Center for Tropical Agriculture (CIAT) between 1975 and 2012. The specimens are held at CIAT’s Arthropod Reference Collection (CIATARC). Eleven species of whiteflies, 14 species of parasitoids and one species of hyperparasitoids are reported. Approximately 66% of the whitefly records belong to Aleurotrachelus socialis and 16% to Bemisia tuberculata. The parasitoids with most records are Encarsia hispida, Amitus macgowni and E. bellottii for A. socialis; and E. sophia for B. tuberculata. The complete dataset is available in Darwin Core Archive format via the Global Biodiversity Information Facility (GBIF).